A systematic review: Influence of intermediate-level language differences on language acquisition and writing competence - Guo, Lichao; Nik Aloesnita, Nik Mohd Alwi; Abdullah Adnan, Mohamed; Li, Changlin (Vytautas Magnus University, Institute of Foreign Language, 2025)
This article reviews existing literature on cross-linguistic influence (CLI) in learners’ acquisition of an additional language, focusing on how awareness of language differences between their primary language and the target language impacts writing competence. The study has its special focus on intermediate-level language differences, specifically expression patterns and usage preferences, and their influence on Chinese English learners’ writing. A systematic search of recent studies (last 15 years) was conducted using Google Scholar and CNKI with keywords such as “cross-linguistic knowledge,” “negative transfer,” and “writing competence.” The findings highlight significant CLI at the intermediate level, particularly in areas such as conjunction use, sentence structure complexity, avoidance of passive voice, and word repetition. These challenges stem primarily from differences in expression patterns between Chinese and English. Contrastive Analysis (CA) emerges as an effective tool for predicting errors, tailoring teaching materials, and explaining linguistic phenomena. However, research remains limited regarding the enhancement of cross-linguistic awareness, especially concerning intermediate-level features like hypotactic and paratactic structures. The study underscores the need for more quantitative and empirical research to develop cross-linguistic competence and refine pedagogical strategies. Further exploration is essential to better understand how language differences influence writing performance and to create effective instructional approaches that address intermediate-level CLI.